Digital risk intelligence and supplier failure in African public infrastructure delivery: evidence from Nigeria - Aondofa Tyozenda; T. P. J. Jato; S. A. Tyoakosu (YAYASAN MITRA PERSADA NUSANTARA, 2026)
Digital risk intelligence (DRI) has emerged as a strategic mechanism for mitigating supplier failures in public infrastructure delivery, particularly in African contexts where project delays, cost overruns, and non-compliance remain pervasive. This review critically examines empirical studies from the last nine years to explore how the dimensions of DRI—predictive analytics, real-time monitoring systems, and e-procurement with automated reporting—interact with supplier performance outcomes in Africa, with a particular focus on Nigeria. Findings indicate that predictive analytics enhances foresight in supplier risk assessment, enabling proactive interventions that reduce delays and cost escalations. Real-time monitoring systems facilitate continuous oversight, early detection of deviations, and improved contractual compliance, while e-procurement and automated reporting strengthen transparency, accountability, and governance mechanisms. Comparative analysis across Nigerian case studies, other African countries, and developed economies reveals both opportunities and constraints, highlighting institutional and infrastructural factors that mediate DRI effectiveness. The review further demonstrates theoretical implications for Agency Theory and Dynamic Capabilities Theory by illustrating how DRI reduces information asymmetry and operationalizes sensing, seizing, and transforming capabilities in procurement organizations. Despite growing evidence of DRI’s potential, gaps remain in longitudinal, comparative, and context-specific empirical research. The study concludes by recommending policy reforms, practical adoption strategies, and targeted empirical investigations to optimize DRI deployment and improve supplier performance in African public infrastructure delivery.